THE FACTORS AFFECTING FINANCIAL PERFORMANCE IN MINING SECTOR COMPANIES 2014-2019 PERIOD - Taristy, Dyana Novita; Hartono, Ulil (Universitas Brawijaya, Indonesia, 2021)
Financial performance is an assessment of the company from achieving predetermined targets. The aim of this research is the influence of leverage, firm size, capital structure, intellectual capital, and environmental cost towards the financial performance of Mining Sector Company listed on the Indonesian Stock Exchange (IDX) in 2014-2019. This research is included in the type of explanation research with quantitative research. Return On Assets (ROA) is used in this case to measure the company's financial performance. In this research, the population consisted of 50 companies, and the obtained samples from the purposive sampling consisted of 10 companies. Multiple linear regression is used to be the analysis technique in this research. This research gets results that leverage, firm size, capital structure, and intellectual capital have not to effect on a company's financial performance. The environmental cost has a significant negative effect on the company's financial performance. The company must maintain the form of its responsibility to the environment by paying attention to the proportion of the budget that must be spent not to impact the acquisition of its financial performance. Next researcher can add or replace the variables that have been researched, replace or extend the period of the research year, increase the sample of companies, or use other sectors listed on the IDX as samples to get different results.